2021
DOI: 10.1155/2021/6664434
|View full text |Cite
|
Sign up to set email alerts
|

Association of Oral Hygiene and Periodontal Health with Third Molar Pericoronitis: A Cross-Sectional Study

Abstract: Background. Pericoronitis is a painful inflammatory condition commonly associated with third molar teeth. The purpose of this study was to investigate the relationship between oral hygiene and periodontal health status and the presence of pericoronitis in semi-impacted third molar teeth. Methods. A cross-sectional study was conducted, and 54 patients having at least one mandibular vertically semi-impacted third molar tooth with or without pericoronitis were consecutively enrolled. Subjects with pericoronitis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Mandibular third molars are sometimes associated with the following conditions: dental caries, pericoronitis, root resorption, periodontitis, infections, cysts, tumors, and mandibular fractures [ 8 ].Therefore, without adequate dental maintenance, it is difficult to protect the mandibular third molar fully from those conditions [ 9 ]. Tai et al reported that dental lesions were observed in approximately 7% and periodontal lesions were observed in approximately 40% of cases of impacted third molars; furthermore, dental and periodontal lesions in adjacent mandibular second molars were sometimes observed [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mandibular third molars are sometimes associated with the following conditions: dental caries, pericoronitis, root resorption, periodontitis, infections, cysts, tumors, and mandibular fractures [ 8 ].Therefore, without adequate dental maintenance, it is difficult to protect the mandibular third molar fully from those conditions [ 9 ]. Tai et al reported that dental lesions were observed in approximately 7% and periodontal lesions were observed in approximately 40% of cases of impacted third molars; furthermore, dental and periodontal lesions in adjacent mandibular second molars were sometimes observed [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the effect of no erupted IMTM extraction on the periodontal tissue of the adjacent second molars has become a controversial clinical issue [ 2 ]. The relevant literature indicates that multiple factors, including preoperative periodontal condition, patient age, type of IMTM impaction, intraoperative flap design, tooth extraction instruments used, suture type and other variables affect the distal periodontal tissue of adjacent second molars after IMTM extraction [ [27] , [28] , [29] , [30] , [31] , [32] , [33] ], and suggests that intraoperative flap design plays a major role. Flap designs, as a basic operation during surgery, not only determine the surgical area and access but are also closely related to periodontal tissue healing [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Impacted third molar are commonly associated with several pathologic conditions. When a tooth starts to erupt, a narrow gap called peri-coronary gap is formed between the tooth crown and the oral mucosa [7]. Impacted third molar often has abnormal position and angulation, which leads to a greater gap between the third molar and adjacent second molar.…”
Section: Id Idmentioning
confidence: 99%